2017
DOI: 10.1155/2017/9272363
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Characteristics and Polymorphic Analysis of Vietnamese Rice Landraces as a Comprehensive Information Resource for Marker-Assisted Selection

Abstract: Next generation sequencing technologies have provided numerous opportunities for application in the study of whole plant genomes. In this study, we present the sequencing and bioinformatic analyses of five typical rice landraces including three indica and two japonica with potential blast resistance. A total of 688.4 million 100 bp paired-end reads have yielded approximately 30-fold coverage to compare with the Nipponbare reference genome. Among them, a small number of reads were mapped to both chromosomes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
(27 reference statements)
1
8
0
Order By: Relevance
“…We observed that the transitional SNPs (C/T and G/A) were more frequent than transversional ones (C/G, T/A, A/C and G/T) in both aromatic rice genomes ( supplementary table S1 , Supplementary Material online), similar to the findings from previous studies ( Huang et al 2009 ; McNally et al 2009 ; Trinh et al 2017 ). Interestingly, the distributions of transition/transversion (Ts/Tv) ratio across the genome of two landraces were extremely similar ( supplementary fig.…”
Section: Resultssupporting
confidence: 89%
“…We observed that the transitional SNPs (C/T and G/A) were more frequent than transversional ones (C/G, T/A, A/C and G/T) in both aromatic rice genomes ( supplementary table S1 , Supplementary Material online), similar to the findings from previous studies ( Huang et al 2009 ; McNally et al 2009 ; Trinh et al 2017 ). Interestingly, the distributions of transition/transversion (Ts/Tv) ratio across the genome of two landraces were extremely similar ( supplementary fig.…”
Section: Resultssupporting
confidence: 89%
“…In this region, 5940 nucleotide sequence variations were found (5149 SNPs and 791 InDels) among the four genotypes with reference to Nipponbare. In earlier studies, this 8.97 Mb to 13.5 Mb centromeric spanning region of chromosome 5 was described as polymorphism desert in wild and cultivated Asian rice genotypes (Krishnan S et al, 2014;Rathinasabapathi et al, 2015;Singhabahu et al, 2017;Trinh et al, 2017). So, going by these literatures, we also call this region of 8.2-14.1 Mb on chromosome 5 as polymorphism desert.…”
Section: Identification and Characterization Of Polymorphic Desert Armentioning
confidence: 87%
“…The interaction between selection and recombination, or linked selection, can have a profound impact on the levels of genetic variation across the genome. Genomic region of severely reduced polymorphism density are considered polymorphism desert and one such desert region has been found on chromosome 5 in previous studies (Krishnan S et al, 2014;Rathinasabapathi et al, 2015;Singhabahu et al, 2017;Trinh et al, 2017). However, evolutionary forces shaping the patterns of such polymorphism desert across genomes remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…This is because of the development in high throughput next generation sequencing capabilities. In the absence of phenotypic information, the genomics has made possible to identify population with adaptive compatibilities on the basis of genetic data (Tian et al 2017;Trinh et al 2017). Ecologists and biologists have been trying to discover genes that support local adaptation in certain species in ecosystems.…”
Section: Fig 2: Summarized Factors That Have Negative Impacts On Biomentioning
confidence: 99%